2021
DOI: 10.1002/cad.20397
|View full text |Cite
|
Sign up to set email alerts
|

The family crisis migration stress framework: A framework to understand the mental health effects of crisis migration on children and families caused by disasters

Abstract: Crisis migration refers to displacement of large numbers of individuals and families from their home countries due to wars, dictatorial governments, and other critical hazards (e.g., hurricanes). Although crisis migration can adversely influence direct and indirect effects on the mental health of adults and their children collectively as families, there is a deficiency in theory that addresses family level processes in this crisis migration context. We propose the Family Crisis Migration Stress Framework, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 87 publications
(114 reference statements)
1
44
0
1
Order By: Relevance
“…In many cases, migration took these young people from a "tight" to a "loose" culture (cf. Vos et al, 2021). The "tight"/"loose" difference can be assumed to be particularly pronounced when it comes to values, norms, and beliefs concerning gender roles, sexuality, and romantic relations.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, migration took these young people from a "tight" to a "loose" culture (cf. Vos et al, 2021). The "tight"/"loose" difference can be assumed to be particularly pronounced when it comes to values, norms, and beliefs concerning gender roles, sexuality, and romantic relations.…”
Section: 4mentioning
confidence: 99%
“…The challenges of bi-cultural stress (cf. Vos et al, 2021) that are unique to migrants and minority members or the potential advantages of bi-or multi-cultural competence (cf. Perez et al, 2021), which is an often-overlooked asset, are further cases in point.…”
Section: The Value Of Theorizing and Evidence Specifically Addressing Young Migrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…
Migration is a challenging global phenomenon that has been a growing trend in recent years [1], [2]. In 2020, it is revealed that approximately 3.6% of the world population were international immigrants [3].
…”
mentioning
confidence: 99%
“…In their contribution, Vos et al (2021) focus on crisis migration (i.e., forms of forced migration caused by natural or human disasters) and their effects on children and families' mental health outcomes. The article highlights the necessity to account for familylevel processes to better understand and improve the mental health and well-being of migrant children.…”
mentioning
confidence: 99%